2016
DOI: 10.7171/jbt.16-2702-004
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing-Based HPV Genotyping Assay Validated in Formalin-Fixed, Paraffin-Embedded Oropharyngeal and Cervical Cancer Specimens

Abstract: Available clinical human papilloma virus (HPV) diagnostics for head and neck cancer have limited sensitivity and/or fail to define the HPV genotype. Common HPV genotyping assays are costly and labor intensive. We sought to develop a next-generation sequencing (NGS)-based HPV genotyping assay that was sensitive enough to work on formalin-fixed paraffin-embedded (FFPE) samples. We developed an ion torrent NGS HPV genotyping assay using barcoded HPV PCR broad-spectrum general primers 5 + /6 + (BSGP)5 + /6 + . To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…In addition to DNA microarray and methylation arrays, deep sequencing such as next-generation sequencing (NGS) has also been widely used to understand genetic changes in cervical cancer [62,63]. For example, one group validated 20 different HPV genotypes in 266 cervical cancer specimens using NGS approach [64]. One study described cervical cytology by deep sequencing to investigate and compare HPV metagenomes for correlation with disease states [65].…”
Section: Systems Biology Approaches In Cervical Cancermentioning
confidence: 99%
“…In addition to DNA microarray and methylation arrays, deep sequencing such as next-generation sequencing (NGS) has also been widely used to understand genetic changes in cervical cancer [62,63]. For example, one group validated 20 different HPV genotypes in 266 cervical cancer specimens using NGS approach [64]. One study described cervical cytology by deep sequencing to investigate and compare HPV metagenomes for correlation with disease states [65].…”
Section: Systems Biology Approaches In Cervical Cancermentioning
confidence: 99%
“…11 HPV typing is feasible in paraffin-embedded tissue specimens. 9,45,80 Progress in Developing Genomic Tests for HPV-Related Neoplasia…”
Section: Hpv Status In Oropharyngeal Carcinoma Affects Prognosismentioning
confidence: 99%
“…39 Genomic methods have recently been described. 9,10,45,80 Cell-free DNA assays for HPV DNA in plasma show promise as a noninvasive measure of HPV þ carcinoma burden, and work is underway to evaluate this approach to monitor treatment efficacy, to identify recurrence, and to enhance early cancer detection. 27,30 A combinatorial approach is envisioned in which plasma is analyzed for viral DNA and for mutations common in carcinoma (eg, in PIK3CA).…”
Section: Hpv Status In Oropharyngeal Carcinoma Affects Prognosismentioning
confidence: 99%
“…Similar studies reported at the time of planning this study, typically combined the HPV consensus primers MY09/11,PGMY or a modified PGMY, which amplify a 450 nt fragment, in combination with 454 sequencing technology [1820]. A recent study utilized the Ion Torrent platform in combination with the HPV broad-spectrum general primers (BSGP5+/6+) on formalin-fixed, paraffin-embedded cancer specimens, showing high sensitivity and specificity [21]. The BSGP5+/6+ primer system was designed by Schmitt et al [22] and consists of a pool of 3 reverse primers and 9 forward primers targeting the L1 gene.…”
Section: Introductionmentioning
confidence: 96%